Upaya Meningkatkan Motivasi dan Hasil Belajar PKn Siswa Kelas VIII-1 SMPN 4 Mataram Melalui Penerapan Pendekatan Cooperative Learning Tipe STAD - Rohayati, Mariana Dwi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
This study aims to determine the effectiveness of cooperative learning approach (CL) type STAD in an effort to improve the motivation of learning mathematics students of class VIII-1 SMP Negeri 4 Mataram. The benefits of this research are as a study material and the material findings in the implementation process real classroom learning. For teachers to improve competence in the learning process and for students to improve learning motivation that impacts on student learning outcomes. Research this is done two cycles, each cycle activity is; planning, execution, observation and reflection. The final result of action in cycle II shows that the teacher's observation scores average (4.21) and student observation results achieved an average score (4.16). While the impact of the increase the motivation to learn is the increase in the achievement of student learning achieves the average value (94.09), that is the success indicator (> 4.0) has been exceeded. Because the indicator of success has been proven research declared successful and stopped in cycle II.